Behavioral, hormonal, and neural alterations induced by social contagion for pain in mice - Baptista-de-Souza, Daniela [UNESP]; Rodrigues Tavares, Lígia Renata [UNESP]; Canto-de-Souza, Lucas [UNESP]; Nunes-de-Souza, Ricardo Luiz [UNESP]; Canto-de-Souza, Azair [UNESP] (Elsevier, 2022)
Neurobiology of social contagion/empathy aims to collaborate with the development of treatments for human disorders characterized by the absence of this response – autism spectrum disorder, schizophrenia, and antisocial personality disorder. Previous studies using sustained aversive stimuli (e.g., neuropathic pain or stress) to induce social contagion behaviors in rodents have demonstrated that these conditions may increase hypernociception, anxiogenic-like effects, and defensive behaviors in cagemates. To amplify the knowledge about behavioral, hormonal, and neural alterations induced by cohabitation with a pair in neuropathic pain, we investigated the effects of this protocol on (i) pain (writhing, formalin, hot plate tests) and depression (sucrose splash test) responses, (ii) the serum levels of corticosterone, testosterone, and oxytocin, (iii) noradrenalin, dopamine and its metabolite (DOPAC and HVA) levels in the amygdaloid complex and insular cortex, (iv) neuronal activation pattern (FosB labeling) in the ventral tegmental area (VTA), paraventricular nucleus of the hypothalamus (PVN) and supraoptic nucleus (SO). One day after weaning, male Swiss mice were housed in pairs for 14 days. Then, they were divided into two groups: sciatic nerve constricted cagemate [CNC; i.e., one animal of each pair was subjected to sciatic nerve constriction (NC)], and cagemate sham (CS; a similar procedure but with no nerve constriction), and housed for further 14 days. After 28 days of cohabiting, four independent groups were subjected to (a) behavioral analyses (Exp. 1) and (b) blood samples collected for Elisa assays of corticosterone, testosterone, and oxytocin (Exp. 2), remotion of brains for the (c) HPLC in the noradrenaline dopamine and metabolites quantification (Exp. 3) or (d) immunoassays analyses for FosB labeling (Exp. 4). Results showed that cohabitation with a conspecific in chronic pain induces hypernociception and antinociception in the writhing and formalin tests, respectively, and anhedonic-like effects in the sucrose splash test. Hormonal results indicated a decrease in plasma corticosterone only in nerve constricted mice, in testosterone (CNC and NC animals), and an increase in oxytocin serum levels. The neurochemical analyses demonstrated that the social contagion for pain protocol increases in dopamine turnover in the amygdala and insula. This assay also revealed an increase in noradrenaline levels and dopamine turnover within the insula of NC mice. In the FosB labeling measure, we observed a rise in the VTA, PVN and SO in the CNC group whereas for the NC group an increase of this activation pattern occurred only in the VTA. Present results suggest the role of hormones (testosterone and oxytocin) and neurotransmitters (dopamine) in the modulation of behavioral changes induced by social contagion in animals cohabitating with a conspecific in pain.
Keywords: Dopamine; Empathy; Mice; Oxytocin; Pain; Social contagion; Testosterone